2013
DOI: 10.1038/ncomms3842
|View full text |Cite
|
Sign up to set email alerts
|

Thymic epithelial cell expansion through matricellular protein CYR61 boosts progenitor homing and T-cell output

Abstract: Thymic epithelial cells (TEC) are heterogeneous stromal cells that generate microenvironments required for the formation of T cells within the thymus. Defects in TEC lead to immunodeficiency or autoimmunity. Here we identify TEC as the major source of cysteinerich protein 61 (CYR61), a matricellular protein implicated in cell proliferation and migration. Binding of CYR61 to LFA-1, ICAM-1 and integrin a6 supports the adhesion of TEC and thymocytes as well as their interaction. Treatment of thymic lobes with rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…First described in cardiovascular development and carcinogenesis, CCN1 now is recognized as a mediator in leukocyte migration and inflammatory processes (15,16) and in the development of the thymus (17). CCN1 exhibits chemoattractant properties for human and murine inflammatory monocytes by promoting their adhesion and migration through integrin CD11b and the cell-surface heparin sulfate proteoglycan syndecan-4 (15,16,(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…First described in cardiovascular development and carcinogenesis, CCN1 now is recognized as a mediator in leukocyte migration and inflammatory processes (15,16) and in the development of the thymus (17). CCN1 exhibits chemoattractant properties for human and murine inflammatory monocytes by promoting their adhesion and migration through integrin CD11b and the cell-surface heparin sulfate proteoglycan syndecan-4 (15,16,(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Positive selection is accompanied by periods of migration interrupted by brief migratory pauses (24). Acting in synergy with chemokines, the ECM components facilitate thymocyte migration and compartmentalization and also support thymocyte adhesion to TECs, with the thymic medulla containing a denser laminin network than the cortex (23,25,26). We found that several groups of ECM-related genes were upregulated in Psmb11 2/2 cTECs (Fig.…”
Section: Psmb11 Regulates Genes Involved In Chemokine Signaling and Cmentioning
confidence: 71%
“…Differential expression of selected genes was independently verified by RT‐PCR including HuCCT1‐YAPS94A cells. RT‐PCR confirmed up‐regulation of YAP target genes ANKRD1, CYR61, CTGF (promoting proliferation), and MFAP5 (promoting tumor vascularization) and down‐regulation of TNFSF10 (encoding tumor necrosis factor–related apoptosis‐inducing ligand (TRAIL); promoting cell death) in YAP overexpressing HuCCT1 cells (Fig. D).…”
Section: Resultsmentioning
confidence: 87%